¿Cómo se convierte 9 = (2x + y) ^ 2-3y-x en forma polar?

¿Cómo se convierte 9 = (2x + y) ^ 2-3y-x en forma polar?
Anonim

Responder:

# r = 9 / (2 (cos ^ 2theta + 1) + 2sin (2theta) -3sintheta-costheta) #

Explicación:

Usaremos:

# x = rcostheta #

# y = rsintheta #

# 9 = (2rcostheta + rsintheta) ^ 2-3rsintheta-rcostheta #

# 9 = r ((2costheta + sintheta) ^ 2-3sintheta-costheta) #

# r = 9 / ((2costheta + sintheta) ^ 2-3sintheta-costheta) #

# r = 9 / (4cos ^ 2 theta + 4costhetasintheta + 2sin ^ 2theta-3sintheta-costheta) #

# r = 9 / (2 (2cos ^ 2theta + sin ^ 2theta) + 2sin (2theta) -3sintheta-costheta) #

# r = 9 / (2 (cos ^ 2theta + 1) + 2sin (2theta) -3sintheta-costheta) #